The Aptian Marls of La Tuilière (Luberon UNESCO Global Geopark, France), a Historical Stratotype - Stephane Legal; Pauline Coster (Geoconservation Research)
The historical stratotype of the Aptian Stage (Cretaceous) was defined in the Luberon UNESCO global geopark in the middle of the 19th century. Due to excessive urbanization launched in the early sixties, the best outcropping conditions are those found at La Tuilière, in the vicinity of Saint-Saturnin-lès-Apt. This is a privileged place, with conservation, educational and valorization measures implemented by the local authorities.